Development of Performance Indicators Based on The Balanced Scorecard Method For Clinics in Surakarta - Asri Alfajri; Siti Dyah Handayani; Arlina Dewi (Universitas Aisyah Pringsewu, 2021)
Balanced scorecard (BSC) is one of the performance appraisal and strategic management tools and has become a popular performance measurement instrument. Apart from being a tool for performance appraisal, the BSC can also be used for strategic management. The use of BSC and KPI (Key Performance Indicators) for strategic management purposes makes it possible to gain competitive advantage. The aims of this research is to develop strategic performance indicators for clinics in the Surakarta area based on 4 balanced scorecard perspectives.This type of research is a qualitative case study with data collection method using FGD (Focus Group Discussion). The sample is 7 clinic employees and 2 clinic owner representatives. Data were analyzed using qualitative content analysis techniques. The FGD results obtained 19 strategic plans and 8 strategic performance indicators based on 4 balanced scorecard perspectives. These indicators consist of 1 financial indicator, 2 customer indicators, 3 internal business indicators and 2 growth and learning indicators. This study develops 8 performance indicators or KPIs based on 4 balanced scorecard perspectives that can be used to assess the organizational performance of health facilities, especially clinics and as strategic management of the organization. Balanced scorecard (BSC) merupakan salah satu alat penilaian kinerja dan manajemen strategis dan telah menjadi instrumen pengukuran kinerja yang popular. Selain sebagai alat untuk penilaian kinerja, BSC juga dapat digunakan untuk manajemen strategis. Penggunaan BSC dan KPI (Key Performance Indicators) untuk tujuan manajemen strategis memungkinkan untuk memperoleh keunggulan kompetitif. Tujuan dari penelitian ini adalah untuk mengembangkan indikator kinerja strategis Klinik di daerah Surakarta berdasarkan 4 perspektif balanced scorecard. Jenis penelitian ini adalah kualitatif studi kasus dengan metode pengambilan data menggunakan FGD (Focus Group Discussion). Sample merupakan 7 orang karyawan Klinik dan 2 orang perwakilan pemilik Klinik. Data dianalisis dengan teknik analisis konten kualitatif.Pada Hasil FGD didapatkan sebanyak 19 rencana strategis dan 8 indikator kinerja strategis berdasarkan 4 perspektif balanced scorecard. Indikator-indikator tersebut terdiri dari 1 indikator keuangan, 2 indikator pelanggan, 3 indikator bisnis internal dan 2 indikator pertumbuhan dan pembelajaran. Penelitian ini mengembangkan 8 indikator kinerja atau KPI berdasarkan 4 perspektif balanced scorecard yang dapat digunakan untuk menilai kinerja organisasi fasilitas kesehatan terutama klinik dan sebagai manajemen strategis organisasi.